The Lower Triassic platy limestone in the Jajce area (Bosnia and Herzegovina) - Kolar-Jurkovšek, Tea; Jurkovšek, Bogdan; Vuks, Valery Ja.; Hrvatović, Hazim; Aljinović, Dunja; Šarić, Ćazim; Skopljak, Ferid (Geologija, 2014)
The study presents palaeontological and sedimentological data of the Lower Triassic strata of the Jajce area in Bosnia and Herzegovina. Four microfacies types were differentiated: coarse grained bioclastic packstones, fine grained bioclastic packstones, laminated mudstone and laminated calcisiltites. Sedimentary characteristics of the depositional environment indicate the distal part of a wide, shallow shelf/ramp, in keeping with some other locations spanning the Dinaride chain. Characteristic ichnofossils and macrofauna are present, including ammonoids, bivalves, and gastropods, dominated by Natiria costata (Münster). Conodont elements provide a biostratigraphic framework. The older part of the section is characterized by the conodont Triassospathodus hungaricus (Kozur & Mostler) and the foraminiferans Nodosaria ex gr. skyphica Efimova, Ammodiscus ex gr. minutus Efimova, Glomospirella triphonensis Baud, Zaninetti & Broennimann and Glomospirella shengi Ho. A younger fauna yields T. triangularis (Bender), Meandrospira cheni (Ho) and M. pusilla (Ho). The older fauna belongs to the T. hungaricus conodont Zone based on presence of Spathian conodont elements, while the younger fauna belongs to the T. triangularis conodont Zone.